Patient-Derived Tumor Organoids: A Platform for Precision Therapy of Colorectal Cancer - Li, Yiran; Wu, Wei; Yao, Jiaxin; Wang, Suidong; Wu, Xiufeng; Yan, Jun (Cell transplantation, 2025)
Colorectal cancer (CRC) represents a significant cause of cancer-related mortality on a global scale. It is a highly heterogeneous cancer, and the response of patients to homogeneous drug therapy varies considerably. Patient-derived tumor organoids (PDTOs) represent an optimal preclinical model for cancer research. A substantial body of evidence from numerous studies has demonstrated that PDTOs can accurately predict a patient’s response to different drug treatments. This article outlines the utilization of PDTOs in the management of CRC across a range of therapeutic contexts, including postoperative adjuvant chemotherapy, palliative chemotherapy, neoadjuvant chemoradiotherapy, targeted therapy, third-line and follow-up treatment, and the treatment of elderly patients. This article delineates the manner in which PDTOs can inform therapeutic decisions at all stages of CRC, thereby assisting clinicians in selecting treatment options and reducing the risk of toxicity and resistance associated with clinical drugs. Moreover, it identifies shortcomings of existing PDTOs, including the absence of consistent criteria for assessing drug sensitivity tests, the lack of vascular and tumor microenvironment models, and the high cost of the technology. In conclusion, despite their inherent limitations, PDTOs offer several advantages, including rapid culture, a high success rate, high consistency, and high throughput, which can be employed as a personalized treatment option for CRC. The use of PDTOs in CRC allows for the prediction of responses to different treatment modalities at various stages of disease progression. This has the potential to reduce adverse drug reactions and the emergence of resistance associated with clinical drugs, facilitate evidence-based clinical decision-making, and guide CRC patients in the selection of personalized medications, thereby advancing the individualized treatment of CRC. Graphical Abstract